2018
DOI: 10.1038/s41598-018-35093-0
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of SIN3 Histone Modifying Complex Components During Development

Abstract: Establishment and maintenance of histone acetylation levels are critical for metazoan development and viability. Disruption of the balance between acetylation and deacetylation by treatment with chemical histone deacetylase (HDAC) inhibitors results in loss of cell proliferation, differentiation and/or apoptosis. Histone deacetylation by the SIN3 complex is essential in Drosophila and mice, as loss of the scaffolding factor SIN3 or the associated HDAC results in lethality. The objective of this study is to elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Interestingly simultaneous inactivation of SIN3S and SIN3L complex subunits in both athp-1;suds-3 and athp-1;hda-3 double mutant animals resulted in fully penetrant sterility (Figure 2C), suggesting redundant functions in the maintenance of germline function. Alternatively, or in addition, athp-1 , hda-3 and suds-3 may play redundant, sin-3 independent functions required for fertility (Barnes et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly simultaneous inactivation of SIN3S and SIN3L complex subunits in both athp-1;suds-3 and athp-1;hda-3 double mutant animals resulted in fully penetrant sterility (Figure 2C), suggesting redundant functions in the maintenance of germline function. Alternatively, or in addition, athp-1 , hda-3 and suds-3 may play redundant, sin-3 independent functions required for fertility (Barnes et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Histone demethylase KDM5B, which is part of the PF1 complex, inhibits genes involved in inflammatory response, cell proliferation and cell adhesion in MDA-MB-231 cell line [ 40 , 41 ]. We previously reported that disrupting the interaction of KDM5B with SIN3A results in decrease in H3K4me3 signal and enhances binding of KDM5B to the promoter of ITGA6 gene [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of SIN3A causes loss of proliferative potential 2123 and depletion of SIN3B inhibits the ability of proliferating cells to exit the cell cycle 21,2426 . Because of the ability of SIN3 complexes to regulate cell differentiation 46 and proliferation in cancer cells, they are drug targets 2730 . Consequently, several inhibitors have been developed and used in clinical trials 31,32 , however success on this has been limited by the lack of specificity of these compounds towards the distinct HDAC1/2 complexes 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Class I HDACs (HDAC1/2/3/8) represent the principle nuclear deacetylases that regulate transcription. HDAC1 and HDAC2 (HDAC1/2) are essential for cellular differentiation, development [4][5][6][7] and function as part of multi-subunit complexes 8 . HDAC1/2 are Zn 2+ -dependent enzymes which catalyse the nucleophilic attack of a Zn 2+bound water molecule to a Zn 2+ -polarized N-ε-acetyl-lysine side-chain carbonyl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation